A Selective Approach to the Resection of Cystic Lesions of the Pancreas: Results From 539 Consecutive Patients - Allen, Peter J. (2006)
OBJECTIVE: To define a group of patients with pancreatic cysts who do not require resection. SUMMARY BACKGROUND DATA: The increased use of cross-sectional imaging has resulted in an increased identification of small, asymptomatic pancreatic cysts. Data have not been available to determine which lesions should be resected. METHODS: All patients evaluated at our institution between January 1995 and January 2005 for the ICD-9 diagnosis of pancreatic cyst were reviewed. Analysis was performed to identify associations between patient and cyst characteristics, and selection of operative or nonoperative management. RESULTS: Pancreatic cysts were evaluated in 539 patients. Initial management was operative in 170 patients (32%), and nonoperative (radiographic follow-up) in 369 patients (68%). Factors associated with initial operative management included presence of a solid component (45% vs. 6%, P < 0.001), larger size of the lesion (mean 4.8 cm vs. 2.4 cm, P = 0.001), and presence of symptoms (44% vs. 16%, P = 0.001). Malignancy was present in 18% (32 of 170) of patients initially resected. Mucinous tumors (n = 18) were the most common malignant histologic subtype. None of the invasive cancers arising from mucinous cysts was <3 cm. Median radiographic follow-up in patients initially managed nonoperatively was 24 months (range, 1–172 months). In 29 patients (8%), changes developed within the cyst that resulted in resection; malignancy was present in 11 of 39 (38%), representing 3% (11 of 369) of all patients being followed radiographically. CONCLUSIONS: Selected patients with cystic lesions <3 cm in diameter and without a solid component may be followed radiographically with a malignancy risk (3% this study) that approximates the risk of mortality from resection. Malignancy within mucinous tumors is associated with size, and small mucinous tumors are very unlikely to be malignant.